Transformasi Digital dalam Manajemen Keuangan: Studi Kasus pada UMKM Indonesia di Era Ekonomi Digital - Mohamad Chaidir; Ruslaini Ruslaini; Dadang Irawan (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study analyzes the impact of digital transformation on the financial management of micro, small, and medium enterprises (MSMEs) in Indonesia in the digital economy era. MSMEs play a crucial role in the national economy but face challenges such as low digital and financial literacy levels, limited technology access, and uneven infrastructure. Digital transformation offers various opportunities, including operational efficiency, financial reporting transparency, and access to fintech-based financial services. However, risks such as data security and resistance to change remain concerns. This research uses a literature review method to identify strategies that can support MSMEs in adopting digital technology. The findings indicate that digital literacy, government support, and technological infrastructure development are key elements in maximizing the benefits of digital transformation. This study provides practical contributions for MSME actors and policymakers to create an ecosystem that supports the sustainability and competitiveness of MSMEs in the digital era.